Composition for model material, molded object, and composition set for inkjet photopolymerization
The composition for model materials in inkjet stereolithography, with balanced monomer ratios and a photopolymerization initiator, addresses brittleness by enhancing bending resistance and maintaining high hardness, enabling durable and detailed 3D printed objects.
Patent Information
- Application Number
- JP2023095829
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
AI Technical Summary
Existing photocurable compositions for 3D printing are too brittle and prone to cracking despite having high hardness, making them difficult to bend without deformation.
A composition for model materials in inkjet stereolithography comprising specific ratios of monofunctional, bifunctional, and polyfunctional ethylenically unsaturated monomers, along with a photopolymerization initiator, to achieve a glass transition temperature of 60°C or higher, ensuring resistance to bending while maintaining hardness.
The composition produces objects that are resistant to bending and deformation, with a Shore D hardness of 65 or more, and a glass transition temperature of 60°C or higher, allowing for detailed and durable 3D printed structures.
Smart Images

Figure 2024176935000001 
Figure 2024176935000002 
Figure 2024176935000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a modeling material composition used in ink-jet stereolithography, a modeled object formed from the modeling material composition, and an ink-jet stereolithography composition set containing the modeling material composition. [Background technology]
[0002] Conventionally, a method for producing a three-dimensional object by continuously forming a cured layer having a predetermined shape by irradiating a photocurable composition with light such as ultraviolet light has been widely known. Among them, a material jet type (inkjet type) optical modeling method (hereinafter also referred to as "material jet optical modeling method"), in which a photocurable composition is discharged from a material jet nozzle and immediately thereafter irradiated with light such as ultraviolet light to cure the composition, thereby laminating cured layers having a predetermined shape to produce a three-dimensional object, has been attracting wide attention as a modeling method that can be realized by a small modeling device (3D printer) that can freely produce a three-dimensional object based on CAD (Computer Aided Design) data.
[0003] It is important to increase the hardness of the resin composition after photocuring so that a three-dimensional object obtained by photocuring a photocurable composition can maintain its shape without sagging or deforming under its own weight after modeling. In order to increase the hardness of a resin composition after photocuring, for example, a composition containing a difunctional or higher monomer as a main component has been proposed (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2007-530724 Summary of the Invention [Problem to be solved by the invention]
[0005] An object molded from the composition described in Cited Document 1 has high hardness and does not sag under its own weight after molding, so it is resistant to deformation. However, it is brittle and weak in bending, and can easily break.
[0006] Therefore, an object of the present invention is to provide a modeling material composition that can obtain a shaped object that is resistant to bending while maintaining high hardness. Another object of the present invention is to provide a shaped object formed from the modeling material composition, and an ink-jet stereolithography composition set that includes the modeling material composition. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention provides the following preferred embodiments.
[0008] [1] A composition for modeling materials for forming model materials by inkjet stereolithography, comprising: 60% by mass or less of a monofunctional ethylenically unsaturated monomer (A) having a homopolymer glass transition temperature of 50° C. or higher; 10% by mass or more and 50% by mass or less of a bifunctional ethylenically unsaturated monomer (B) having a homopolymer glass transition temperature of 50° C. or more; A polyfunctional thiol monomer (C) of 5% by mass or more and 20% by mass or less; Contains a photopolymerization initiator (D), The content of trifunctional or higher ethylenically unsaturated monomers is less than 10% by mass based on the total mass of the composition. A model material composition, wherein a molded object made from the composition has a glass transition temperature of 60°C or higher. [2] The composition according to [1], wherein the content of the oligomer is 20 mass% or less based on the total mass of the composition. [3] The composition according to [2], wherein the oligomer is at least one selected from the group consisting of a urethane (meth)acrylate oligomer, an epoxy (meth)acrylate oligomer, and a polyester (meth)acrylate oligomer. [4] The composition according to any one of [1] to [3], wherein the polyfunctional thiol monomer (C) contains a trifunctional or tetrafunctional thiol monomer. [5] The composition according to [4], wherein the trifunctional thiol monomer comprises 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione or trimethylolpropane tris(3-mercaptopropionate). [6] The composition according to [4], wherein the tetrafunctional thiol monomer includes pentaerythritol tetrakis(3-mercaptobutyrate) or pentaerythritol tetrakis(3-mercaptopropionate). [7] The composition according to any one of [1] to [6], wherein the content of the photopolymerization initiator (D) is 0.1 mass % or more and 15 mass % or less based on the total mass of the composition. [8] The composition according to any one of [1] to [7], wherein the degree of bending calculated as the deflection when the center of a 40 mm × 5 mm × 2 mm test piece is pressed with a load of 5 kg at 25°C and 50% RT is 12 mm or more. [9] The composition according to any one of [1] to [8], wherein a shaped object produced from the composition has a Shore D hardness of 65 or more.
[10] The composition according to any one of [1] to [9], wherein the component (A) contains isobornyl acrylate.
[11] The composition according to any one of [1] to
[10] , wherein the component (A) contains acryloylmorpholine.
[12] The composition according to any one of [1] to
[11] , wherein the light source used in the inkjet stereolithography is an LED.
[13] A shaped object produced from the composition according to any one of [1] to
[12] .
[14] An inkjet stereolithography composition set comprising the composition according to any one of [1] to
[12] and a support material composition for forming a support material by inkjet stereolithography. Effect of the Invention
[0009] According to the present invention, it is possible to provide a model material composition capable of obtaining a shaped object that is resistant to bending while maintaining high hardness, a shaped object formed from the model material composition, and an inkjet photopolymerization composition set containing the model material composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0011] <Composition for model material> The modeling material composition of the present invention contains 60% by mass or less of a monofunctional ethylenically unsaturated monomer (A) having a homopolymer glass transition temperature (Tg) of 50° C. or more, 10% by mass or more and 50% by mass or less of a bifunctional ethylenically unsaturated monomer (B) having a homopolymer glass transition temperature of 50° C. or more, 5% by mass or more and 20% by mass or less of a polyfunctional thiol monomer (C), and a photopolymerization initiator (D), and the content of the trifunctional or higher ethylenically unsaturated monomer is less than 10% by mass based on the total mass of the composition, and the glass transition temperature of a molded object molded from the composition is 60° C. or more. In the present invention, "(meth)acrylate" is a general term for acrylate and methacrylate, and means one or both of acrylate and methacrylate. The same applies to "(meth)acryloyl", "(meth)acrylic", etc.
[0012] In order to increase the hardness of a molded object, it is usually considered to blend 1) a trifunctional or higher polyfunctional polymerizable monomer or 2) a polymerizable monomer with a high glass transition temperature of the homopolymer as a main component into a composition for modeling materials. A molded object obtained from such a composition has many crosslinking points and a high glass transition temperature, and therefore may have sufficient hardness, but is brittle, weak in bending, and easily broken. Therefore, the present inventors have investigated a means for solving the above problems regarding a composition mainly composed of monofunctional and bifunctional polymerizable monomers in order to avoid excessive polymerization, and have found that blending a specific thiol monomer can obtain a molded object that is strong in bending while maintaining hardness, even if the composition mainly consists of monofunctional and bifunctional polymerizable monomers. The reason for this is not necessarily clear, but it is thought that the thiol monomer contained in the composition makes it difficult for crosslinking points to be densely packed during hardening, thereby preventing the composition from being over-hardened and becoming brittle.
[0013] (Monofunctional ethylenically unsaturated monomer (A)) The modeling material composition of the present invention contains a monofunctional ethylenically unsaturated monomer (A) having a homopolymer glass transition temperature of 50° C. or higher (hereinafter, may be simply referred to as "monofunctional monomer (A)") in an amount of 60 mass % or less based on the total mass of the composition. In the present invention, the monofunctional ethylenically unsaturated monomer refers to a monomer having one ethylenic double bond in the molecule, which has the property of being cured by energy rays. The monofunctional monomer (A) may contain one thiol group. Specific examples include alkyl (meth)acrylates having a linear or branched alkyl group; (meth)acrylates having a cyclic structure such as an alicyclic structure, an aromatic ring structure, or a heterocyclic structure in the molecule; and monofunctional ethylenically unsaturated monomers containing nitrogen atoms such as (meth)acrylamide. The monofunctional monomer (A) may be used alone or in a mixture of two or more types. In this specification, an alicyclic structure refers to an aliphatic cyclic structure in which carbon atoms are bonded in a ring, an aromatic ring structure refers to an aromatic cyclic structure in which carbon atoms are bonded in a ring, and a heterocyclic structure refers to a structure in which carbon atoms and one or more heteroatoms are bonded in a ring.
[0014] The monofunctional monomer (A) has a glass transition temperature of 50° C. or higher when made into a homopolymer. If the glass transition temperature is lower than 50° C., the molded object obtained by curing the modeling material composition of the present invention may deform under ambient conditions. The glass transition temperature of the monofunctional monomer (A) when made into a homopolymer is preferably 60° C. or higher, more preferably 70° C. or higher, even more preferably 80° C. or higher, even more preferably 90° C. or higher, particularly preferably 100° C. or higher, even more particularly preferably 110° C. or higher, and extremely preferably 120° C. or higher. If the glass transition temperature is equal to or higher than the lower limit, deformation does not occur under ambient conditions, and a molded object having high hardness is easily obtained. The upper limit of the glass transition temperature is not particularly limited, but is usually 300° C. or lower, preferably 200° C. or lower.
[0015] The glass transition temperature of a homopolymer of a monomer can be measured, for example, by differential scanning calorimetry (DSC). The glass transition temperature of a homopolymer may depend on the degree of polymerization, but if a homopolymer with a weight-average molecular weight of 20,000 or more is produced and measured, the effect of the degree of polymerization can be ignored.
[0016] Examples of alkyl(meth)acrylates having a linear or branched alkyl group and having a homopolymer glass transition temperature of 50° C. or higher include alkyl(meth)acrylates having a linear or branched alkyl group preferably having 5 to 25 carbon atoms, more preferably 6 to 20 carbon atoms.
[0017] Examples of the (meth)acrylate having an alicyclic structure and having a homopolymer glass transition temperature of 50° C. or higher include (meth)acrylates having an alicyclic structure preferably having 8 to 30 carbon atoms, more preferably having 10 to 15 carbon atoms. Specific examples include isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate.
[0018] Examples of (meth)acrylates having an aromatic ring structure and having a homopolymer glass transition temperature of 50° C. or higher include (meth)acrylates having an aromatic ring structure preferably having 8 to 30 carbon atoms, more preferably having 9 to 20 carbon atoms. Specific examples include 2-phenoxyethyl methacrylate.
[0019] Examples of (meth)acrylates having a heterocyclic structure and having a homopolymer glass transition temperature of 50° C. or higher include (meth)acrylates having a heterocyclic structure preferably having 8 to 30 carbon atoms, more preferably having 9 to 20 carbon atoms.
[0020] In addition, examples of the nitrogen atom-containing monofunctional ethylenically unsaturated monomer different from the above (meth)acrylates include (meth)acrylamides (e.g., (meth)acryloylmorpholine, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-(2-hydroxyethyl)acrylamide, N-isopropylacrylamide, etc.).
[0021] Among these, the monofunctional monomer (A) is preferably a monofunctional ethylenically unsaturated monomer having a cyclic structure in the molecule. When the monofunctional monomer (A) has a cyclic structure in the molecule, it is easier to obtain a shaped object that is strong against bending while maintaining high hardness. In a preferred embodiment of the present invention, the monofunctional monomer (A) preferably contains isobornyl acrylate. When the monofunctional monomer (A) contains isobornyl acrylate, the hardness of the obtained shaped object can be increased.
[0022] In another embodiment of the present invention, the monofunctional monomer (A) preferably contains acryloyl morpholine. When the monofunctional monomer (A) contains acryloyl morpholine, the glass transition temperature of the resulting molded object becomes higher, and the molded object is less likely to deform at the ambient temperature. Furthermore, when the modeling material composition of the present invention is used in combination with a water-soluble supporting material composition as described below, acryloyl morpholine, which is a polar monomer and easily soluble in a polar solvent such as water used as a removal solvent for removing the supporting material, can be used in the supporting material composition. When the modeling material composition contains acryloyl morpholine used in the supporting material composition, the surface tension is high, so that the interface between the supporting material and the modeling material is prevented from mixing, while the polarities of the supporting material and the modeling material are brought closer to each other, thereby improving the wettability of the supporting material and the modeling material. Therefore, when the modeling material composition contains acryloyl morpholine, the effect of maintaining the boundary between the modeling material and the supporting material during the production of the molded object is enhanced, and a molded object can be obtained with good dimensional accuracy. The monofunctional monomer (A) may contain both isobornyl acrylate and acryloylmorpholine.
[0023] The content of the monofunctional monomer (A) in the modeling material composition is 60% by mass or less based on the total mass of the composition. If the content of the monofunctional monomer (A) exceeds 60% by mass, the hardness of the molded object becomes too high and becomes brittle. The content of the monofunctional monomer (A) is preferably 55% by mass or less, more preferably 50% by mass or less, even more preferably 49% by mass or less, even more preferably 48% by mass or less, particularly preferably 47% by mass or less, even more particularly preferably 45% by mass or less, and extremely preferably 42% by mass or less. If the content of the monofunctional monomer (A) is less than the upper limit, it is easier to obtain a molded object that is strong against bending while maintaining high hardness. The lower limit of the content of the monofunctional monomer (A) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. If the content of the monofunctional monomer (A) is more than the lower limit, it is easier to adjust the viscosity of the modeling material composition, and it is easier to control the crosslinking density, and it is easier to obtain a molded object that is strong against bending and does not easily break.
[0024] (Difunctional ethylenically unsaturated monomer (B)) The model material composition of the present invention contains a bifunctional ethylenically unsaturated monomer (B) having a homopolymer glass transition temperature of 50° C. or higher (hereinafter, may be simply referred to as "bifunctional monomer (B)") in an amount of 10% by mass or more and 50% by mass or less based on the total mass of the composition. In the present invention, the bifunctional ethylenically unsaturated monomer refers to a monomer having two ethylenic double bonds in the molecule, which have the property of being cured by energy rays. The bifunctional monomer (B) may contain one thiol group. Specific examples include linear or branched alkylene glycol di(meth)acrylates and cyclic structure-containing di(meth)acrylates. The bifunctional monomer (B) may be used alone or in combination of two or more types.
[0025] The bifunctional monomer (B) has a glass transition temperature of 50° C. or higher when made into a homopolymer. If the glass transition temperature is lower than 50° C., the molded object obtained by curing the model material composition may deform under ambient conditions. The glass transition temperature of the bifunctional monomer (B) when made into a homopolymer is preferably 60° C. or higher, more preferably 65° C. or higher, even more preferably 70° C. or higher, even more preferably 80° C. or higher, particularly preferably 90° C. or higher, and extremely preferably 100° C. or higher. If the glass transition temperature is equal to or higher than the lower limit, deformation does not occur under ambient conditions, and a molded object having high hardness is easily obtained. The upper limit of the glass transition temperature is not particularly limited, but is usually 300° C. or lower, preferably 200° C. or lower.
[0026] The linear or branched alkylene glycol di(meth)acrylate having a homopolymer glass transition temperature of 50° C. or higher is preferably a linear or branched alkylene glycol di(meth)acrylate having 10 to 17 carbon atoms, such as tripropylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, etc.
[0027] The cyclic structure-containing di(meth)acrylate having a homopolymer glass transition temperature of 50° C. or higher is preferably a cyclic structure-containing di(meth)acrylate having 25 to 31 carbon atoms, and examples thereof include ethoxylated (3) bisphenol A diacrylate and ethoxylated (4) bisphenol A diacrylate.
[0028] Among these, the bifunctional monomer (B) preferably contains a linear or branched alkylene glycol di(meth)acrylate, more preferably contains at least one of tripropylene glycol diacrylate and dipropylene glycol diacrylate, and particularly preferably contains tripropylene glycol diacrylate. When the bifunctional monomer (B) contains a linear or branched alkylene glycol di(meth)acrylate, the hardness of the obtained shaped object can be increased.
[0029] The content of the bifunctional monomer (B) in the model material composition is 10% by mass or more and 50% by mass or less based on the total mass of the composition. If the content of the bifunctional monomer (B) is less than 10% by mass, the hardness of the molded object is insufficient. If the content of the bifunctional monomer (B) is more than 50% by mass, the hardness of the molded object becomes too high and brittle. The content of the bifunctional monomer (B) is preferably 20% by mass or more, more preferably 24% by mass or more, even more preferably 25% by mass or more, even more preferably 26% by mass or more, particularly preferably 30% by mass or more, and preferably 45% by mass or less, more preferably 39% by mass or less, and even more preferably 38% by mass or less. If the content of the bifunctional monomer (B) is the lower limit or more and the upper limit or less, it is easier to obtain a molded object that is strong against bending while maintaining high hardness.
[0030] The total content of the monofunctional monomer (A) and the bifunctional monomer (B) is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 73% by mass or more, based on the total mass of the composition, and is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 87% by mass or less. When the total content of the monofunctional monomer (A) and the bifunctional monomer (B) is equal to or more than the lower limit and equal to or less than the upper limit, it is easier to obtain a shaped product that is strong against bending while maintaining high hardness.
[0031] The mass ratio of the monofunctional monomer (A) to the bifunctional monomer (B) in the composition (mass of the monofunctional monomer (A):mass of the bifunctional monomer (B)) is preferably 0.5:1 to 5:1, more preferably 0.8:1 to 4.5:1, even more preferably 1:1 to 4:1, and even more preferably 1.5:1 to 3.5:1. When the mass ratio of the monofunctional monomer (A) to the bifunctional monomer (B) in the composition is within the above range, it is easier to obtain a shaped product that is strong against bending while maintaining high hardness.
[0032] (Multifunctional thiol monomer (C)) The modeling material composition of the present invention contains the polyfunctional thiol monomer (C) in an amount of 5% by mass or more and 20% by mass or less based on the total mass of the composition. In the present invention, the polyfunctional thiol monomer may refer to a compound having two or more thiol groups (-SH) in the molecule and having a molecular weight of 1000 or less. When the modeling material composition of the present invention contains the polyfunctional thiol monomer (C), a molded object that is particularly strong against bending can be obtained. In this specification, the polyfunctional thiol monomer (C) may contain up to two ethylenic double bonds. Moreover, the polyfunctional thiol monomer (C) may be used alone or in a mixture of two or more kinds.
[0033] The content of the polyfunctional thiol monomer (C) in the model material composition is 5% by mass or more and 20% by mass or less based on the total mass of the composition. When the content of the polyfunctional thiol monomer (C) is less than 5% by mass, the proportion of the polyfunctional thiol monomer is low, crosslinking of the acrylic monomer becomes dominant, and crosslinking points tend to be dense, so that the modeled object obtained from the model material composition of the present invention is weak in bending. When the content of the polyfunctional thiol monomer (C) exceeds 20% by mass, crosslinking by the thiol monomer becomes dominant, and the crosslinking density is too low, so that the hardness of the modeled object decreases. The content of the polyfunctional thiol monomer (C) in the model material composition is preferably 6% by mass or more, more preferably 8% by mass or more, and preferably 17% by mass or less, more preferably 14% by mass or less. When the content of the polyfunctional thiol monomer (C) is equal to or more than the lower limit and equal to or less than the upper limit, it is easier to obtain a modeled object that is strong in bending while maintaining high hardness.
[0034] Examples of polyfunctional thiol monomers include bifunctional thiol monomers such as 1,2-ethanedithiol, 1,4-benzenedithiol, and 1,4-bis(3-mercaptobutyryloxy)butane; trifunctional thiol monomers; and tetrafunctional thiol monomers. However, it is preferable that the polyfunctional thiol monomer (C) contains a trifunctional or tetrafunctional thiol monomer, since this makes it easier to obtain a shaped object that is resistant to bending while maintaining high hardness.
[0035] Examples of trifunctional thiol monomers include trifunctional alkyl thiol monomers, trifunctional ester-type thiol monomers, and trifunctional ether-type thiol monomers. Of these, trifunctional ester-type thiol monomers or trifunctional ether-type thiol monomers are preferred because they are more likely to produce shaped objects that are resistant to bending while maintaining high hardness. Examples of trifunctional ester-type thiol monomers include 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, trimethylolpropane tris(3-mercaptobutyrate), etc. Examples of trifunctional ether-type thiol monomers include pentaerythritol trippropanethiol, etc.
[0036] Examples of tetrafunctional thiol monomers include tetrafunctional alkyl thiol monomers, tetrafunctional ester-type thiol monomers, and tetrafunctional ether-type thiol monomers. Among these, tetrafunctional ester-type thiol monomers or tetrafunctional ether-type thiol monomers are preferred because they are more likely to produce shaped objects that are resistant to bending while maintaining high hardness. Examples of tetrafunctional ester-type thiol monomers include pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), etc. Examples of tetrafunctional ether-type thiol monomers include pentaerythritol tetrapropanethiol, etc.
[0037] Among the trifunctional thiol monomers, it is preferable to include at least one of 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione and trimethylolpropane tris(3-mercaptopropionate), since this makes it easier to obtain shaped objects that are resistant to bending while maintaining high hardness. Among the tetrafunctional thiol monomers, it is preferable to include at least one of pentaerythritol tetrakis(3-mercaptobutyrate) and pentaerythritol tetrakis(3-mercaptopropionate). These thiol monomers may be used alone or in combination of two or more. When used in combination, the combination may be any of a combination of two or more trifunctional thiol monomers, a combination of two or more tetrafunctional thiol monomers, or a combination of one or more trifunctional thiol monomers and one or more tetrafunctional thiol monomers.
[0038] (Other polymerizable compounds) In the present invention, the model material composition may contain a monofunctional ethylenically unsaturated monomer other than the monofunctional monomer (A), that is, a monofunctional ethylenically unsaturated monomer having a glass transition temperature of less than 50°C as a homopolymer. Examples of such monofunctional ethylenically unsaturated monomers include phenoxyethyl acrylate, phenoxyethoxyethyl acrylate, isoamyl acrylate, lauryl (meth)acrylate, octyl acrylate, isooctyl (meth)acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, tridecyl (meth)acrylate, isomyristyl acrylate, isostearyl acrylate, 2-ethylhexyl acrylate, 2-ethylhexyl-diglycol acrylate, 4-hydroxybutyl acrylate, methoxydiethylene glycol acrylate, methoxytriethylene glycol acrylate, ethoxydiethylene glycol acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, 2-ethylhexyl carbitol acrylate, stearyl acrylate, and stearyl methacrylate. The monofunctional ethylenically unsaturated monomers other than the monofunctional monomer (A) may be used alone or in combination of two or more.
[0039] When a monofunctional ethylenically unsaturated monomer other than the monofunctional monomer (A) is contained, depending on the amount, the glass transition temperature of the molded object obtained from the composition may decrease, and the molded object may soften under ambient temperature conditions. Therefore, the content is preferably 10 mass% or less, more preferably 5 mass% or less, based on the total mass of the composition. In addition, the lower limit is not particularly limited, and the composition may not contain any monofunctional ethylenically unsaturated monomer other than the monofunctional monomer (A), and preferably the model material composition of the present invention does not contain any monofunctional ethylenically unsaturated monomer other than the monofunctional monomer (A) (i.e., 0 mass%).
[0040] In the present invention, the model material composition may contain a difunctional ethylenically unsaturated monomer other than the difunctional monomer (B), i.e., a difunctional ethylenically unsaturated monomer having a homopolymer glass transition temperature of less than 50° C. Examples of such a difunctional ethylenically unsaturated monomer include tetraethylene glycol di(meth)acrylate and propoxylated (2) neopentyl glycol di(meth)acrylate. The difunctional ethylenically unsaturated monomer other than the difunctional monomer (B) may be used alone or in combination of two or more.
[0041] When a bifunctional ethylenically unsaturated monomer other than the bifunctional monomer (B) is contained, depending on the amount, the glass transition temperature of the model obtained from the composition may decrease, and the model may soften under ambient temperature conditions. Therefore, the content is preferably 10 mass% or less, more preferably 5 mass% or less, based on the total mass of the composition. The lower limit is not particularly limited, and the composition may not contain any bifunctional ethylenically unsaturated monomer other than the bifunctional monomer (B), and preferably the model material composition of the present invention does not contain any bifunctional ethylenically unsaturated monomer other than the bifunctional monomer (B) (i.e., 0 mass%).
[0042] In the present invention, the content of the trifunctional or higher ethylenically unsaturated monomer in the model material composition is less than 10% by mass based on the total mass of the composition. Here, the trifunctional or higher ethylenically unsaturated monomer may refer to a monomer having three or more ethylenic double bonds in the molecule that have the property of being cured by energy rays. The trifunctional or higher ethylenically unsaturated monomer may contain a thiol group.
[0043] When the tri- or higher functional ethylenically unsaturated monomer is contained at 10% by mass or more, the number of reaction sites becomes too large, so that the hardness of the model obtained from the model material composition becomes too high and the model becomes easily broken. The content of the tri- or higher functional ethylenically unsaturated monomer is preferably 8% by mass or less, more preferably 5% by mass or less. The lower limit is not particularly limited, and the composition may not contain any tri- or higher functional ethylenically unsaturated monomer at all, and preferably the model material composition of the present invention does not contain any tri- or higher functional ethylenically unsaturated monomer (i.e., 0% by mass).
[0044] The glass transition temperature of the trifunctional or higher ethylenically unsaturated monomer when it is made into a homopolymer is preferably 50°C or higher, more preferably 70°C or higher, and even more preferably 90°C or higher. When the glass transition temperature of the trifunctional or higher ethylenically unsaturated monomer when it is made into a homopolymer is equal to or higher than the lower limit, it is easier to obtain a shaped object that is strong against bending while maintaining high hardness. Examples of such trifunctional or higher ethylenically unsaturated monomers include pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glycerin propoxy tri(meth)acrylate, and pentaerythritol ethoxy tetra(meth)acrylate. Only one type of trifunctional or higher ethylenically unsaturated monomer may be included, or two or more types may be included.
[0045] The modeling material composition of the present invention may contain a polymerizable compound other than the above-mentioned monomer. Examples of such polymerizable compounds include oligomers. The oligomer may refer to a component having the property of being polymerized and cured by irradiation with active energy rays. In this specification, the term "oligomer" refers to a polymer having a weight average molecular weight M w The weight average molecular weight M of the oligomer is 500 to 10,000. w The weight average molecular weight M of the oligomer is preferably 800 or more, more preferably more than 1,000. w When the weight average molecular weight M is within the above range, a shaped product having high hardness and high bending resistance can be obtained. w means a weight average molecular weight in terms of polystyrene measured by GPC (gel permeation chromatography). As the oligomer, only one type may be used, or two or more types may be used in combination.
[0046] Examples of the oligomer include urethane (meth)acrylate oligomer, epoxy (meth)acrylate oligomer, polyester (meth)acrylate oligomer, polyether (meth)acrylate oligomer, etc., and it is preferable to include at least one selected from the group consisting of urethane (meth)acrylate oligomer, epoxy (meth)acrylate oligomer, and polyester (meth)acrylate oligomer, from the viewpoint of easily obtaining a shaped object that is strong against bending while maintaining high hardness. As the oligomer, either a monofunctional oligomer or a multifunctional oligomer having two or more functionalities may be used, but a multifunctional oligomer having two or more functionalities is preferable, and a bifunctional oligomer is more preferable.
[0047] The glass transition temperature of the oligomer is preferably 0° C. or higher, more preferably 5° C. or higher, even more preferably 10° C. or higher, and preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 100° C. or lower. When the glass transition temperature of the oligomer is equal to or higher than the above-mentioned lower limit and equal to or lower than the above-mentioned upper limit, a shaped article that is resistant to bending while maintaining high hardness is easily obtained.
[0048] When the modeling material composition of the present invention contains an oligomer, the content thereof is preferably 20% by mass or less, more preferably 18% by mass or less, and even more preferably 15% by mass or less, based on the total mass of the modeling material composition. The lower limit is not particularly limited, and the lower limit of the oligomer content may be 0% by mass, and is preferably 1% by mass or more, and more preferably 5% by mass or more. When the oligomer content is within the above range, it is easy to obtain a shaped object that is strong against bending while maintaining high hardness while maintaining the viscosity of the modeling material composition in an appropriate range.
[0049] The content of the polymerizable compound in the model material composition of the present invention is preferably 70 to 94.9% by mass, and may be, for example, 75 to 93% by mass, or 80 to 92% by mass, based on the total mass of the model material composition. When the content of the polymerizable compound is within the above range, it is easy to obtain a shaped object that is strong against bending while maintaining high hardness.
[0050] In the model material composition of the present invention, the mass ratio of the polymerizable compound to the thiol monomer (C) (mass of the polymerizable compound: mass of the thiol monomer (C)) is preferably 3:1 to 20:1, more preferably 4:1 to 18:1, even more preferably 5:1 to 17:1, still more preferably 6:1 to 16:1, and particularly preferably 7:1 to 15:1. When the mass ratio of the polymerizable compound to the thiol monomer (C) in the composition is within the above range, it is easier to obtain a shaped object that is strong against bending while maintaining high hardness.
[0051] (Photopolymerization initiator (D)) The modeling material composition of the present invention contains a photopolymerization initiator (D). The photopolymerization initiator is not particularly limited as long as it is a compound that promotes a radical reaction when irradiated with ultraviolet light, near ultraviolet light, or light having a wavelength in the visible light region. Examples of the photopolymerization initiator include an alkylphenone compound, an acylphosphine oxide compound, an anthraquinone compound, and a thioxanthone compound. Examples of the alkylphenone compounds include benzoin compounds (e.g., benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isobutyl ether, etc.); acetophenone compounds (e.g., acetophenone, 2,2-diethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 2-hydroxy-2-methyl-phenyl-1-propanone, diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, etc.); ketalphenone compounds (e.g., acetophenone dimethyl ketal, benzyl dimethyl ketal, etc.); and benzophenone compounds (e.g., benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 4,4'-bismethylaminobenzophenone, etc.). Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. Examples of the anthraquinone compound include 2-ethylanthraquinone, 2-t-butylanthraquinone, 2-chloroanthraquinone, and 2-amylanthraquinone. Examples of the thioxanthone compound include 2,4-diethylthioxanthone, 2-isopropylthioxanthone, and 2-chlorothioxanthone. These compounds may be used alone or in combination of two or more.Among these, it is preferable to include at least one of an alkylphenone compound or an acylphosphine oxide compound, and it is more preferable to include at least one of an acetophenone compound or an acylphosphine oxide compound. In addition, as the photopolymerization initiator, a commercially available product may be used. Examples of such commercially available products include Omnirad TPO and Omnirad 1173 from IGM Resins.
[0052] The content of the photopolymerization initiator (D) in the model material composition may be appropriately determined depending on the type of polymerizable compound used, its content, etc. In one embodiment of the present invention, the content of the photopolymerization initiator is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the total mass of the model material composition, and is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less. When the content of the photopolymerization initiator (D) is equal to or more than the lower limit and equal to or less than the upper limit, the unreacted polymerization components can be reduced, the curing property of the model material composition can be sufficiently increased, and the influence of the unreacted photopolymerization initiator on the shaped object over time (for example, discoloration such as yellowing) can be suppressed.
[0053] The model material composition may contain other additives as necessary within the range that does not impair the effects of the present invention. Examples of other additives include storage stabilizers, surface conditioners, antioxidants, UV absorbers, light stabilizers, polymerization inhibitors, chain transfer agents, fillers, diluting solvents, thickeners, colorants, etc.
[0054] The model material composition of the present invention may further contain a colorant. However, when the model material composition of the present invention is a colorless and transparent clear composition, it does not contain a colorant.
[0055] The colorant is not particularly limited, but since the modeling material composition of the present invention is non-aqueous, a pigment that is easily dispersed uniformly in a non-aqueous medium and a dye that is easily dissolved are preferable. The colorant may be used alone or in combination of two or more kinds.
[0056] The pigment may be either inorganic or organic. Examples of inorganic pigments include titanium oxide, zinc oxide, lithopone, iron oxide, aluminum oxide, silicon dioxide, kaolinite, montmorillonite, talc, barium sulfate, calcium carbonate, silica, alumina, cadmium red, red iron oxide, molybdenum red, chrome vermilion, molybdate orange, yellow lead, chrome yellow, cadmium yellow, yellow iron oxide, titanium yellow, chrome oxide, pyridian, cobalt green, titanium cobalt green, cobalt chrome green, ultramarine blue, Prussian blue, cobalt blue, cerulean blue, manganese violet, cobalt violet, and mica. Examples of organic pigments include azo, azomethine, polyazo, phthalocyanine, quinacridone, anthraquinone, indigo, thioindigo, quinophthalone, benzimidazolone, and isoindoline organic pigments. Carbon black made of acidic, neutral or basic carbon may also be used. Furthermore, hollow particles of crosslinked acrylic resin may also be used as the organic pigment.
[0057] The colorant can be dispersed using a dispersing device such as a bead mill, a ball mill, a sand mill, an attritor, a roll mill, a jet mill, a homogenizer, a paint shaker, a kneader, an agitator, a Henschel mixer, a colloid mill, an ultrasonic homogenizer, a pearl mill, a wet jet mill, etc., or a mixer such as a line mixer, etc. After dispersing the colorant, classification treatment may be performed using a centrifuge, a filter, a cross flow, etc., for the purpose of removing coarse particles of the colorant.
[0058] The content of the colorant is appropriately selected depending on the color and purpose of use, but from the viewpoints of image density and storage stability, it is preferably 0.05 to 30 mass %, more preferably 0.1 to 10 mass %, based on the total mass of the model material composition.
[0059] From the viewpoint of improving the ejection properties from an inkjet nozzle, the viscosity of the model material composition of the present invention is preferably 3 to 100 mPa·s at 25°C, more preferably 5 to 90 mPa·s, even more preferably 5 to 70 mPa·s, and even more preferably 5 to 60 mPa·s. The viscosity can be measured using an R100 type viscometer in accordance with JIS Z 8803. The viscosity of the model material composition can be adjusted to within the above range by appropriately adjusting the type and / or amount of the polymerizable compound, the type and / or amount of the polyfunctional thiol monomer (C), etc.
[0060] The molded object obtained from the modeling material composition of the present invention has a glass transition temperature that does not deform under ambient conditions. Therefore, the glass transition temperature of the molded object formed from the modeling material composition of the present invention is 60°C or higher. If the glass transition temperature of the molded object is less than 60°C, the molded object may deform under ambient conditions. The glass transition temperature of the molded object obtained from the modeling material composition of the present invention may be preferably 65°C or higher, 66°C or higher, 67°C or higher, 68°C or higher, 69°C or higher, 70°C or higher, 72°C or higher, 73°C or higher, 75°C or higher, 76°C or higher, 82°C or higher, or 86°C or higher. The glass transition temperature of the molded object being equal to or higher than the lower limit means that the molded object obtained from the modeling material composition of the present invention is unlikely to deform under ambient conditions. The glass transition temperature of the molded object can be equal to or higher than the lower limit by, for example, appropriately adjusting the type and / or amount of the polymerizable compound constituting the modeling material composition. The upper limit of the glass transition temperature may usually be 120°C. The glass transition temperature of a shaped article obtained from the model material composition of the present invention can be measured, for example, by using a differential calorimeter according to the method described later in the Examples.
[0061] A molded object that is particularly strong against bending can be obtained from the modeling material composition of the present invention. Therefore, the degree of bending calculated as the deflection when the center of a 40 mm x 5 mm x 2 mm test piece made from the modeling material composition of the present invention is pressed with a load of 5 kg at 25°C and 50% RT is preferably 12 mm or more, more preferably 14 mm or more, even more preferably 15 mm or more, even more preferably 16 mm or more, particularly preferably 17 mm or more, even more particularly preferably 18 mm or more, and extremely preferably exceeds 18 mm. The degree of bending being equal to or more than the lower limit means that the molded object obtained from the modeling material composition of the present invention does not break even when a load is applied, and is strong against bending. The degree of bending can be made equal to or more than the lower limit by, for example, appropriately adjusting the type and / or amount of the polymerizable compound constituting the modeling material composition, the type and / or amount of the polyfunctional thiol monomer, etc. The upper limit of the degree of bending is 20 mm. The degree of bending can be measured by the method described in the Examples below.
[0062] In the present invention, "bending" is evaluated by the bending test, and is different from the conventionally evaluated "bending stress" and "bending modulus". Usually, "bending stress" represents the force generated inside a test piece when a load is applied to the test piece, and "bending modulus" represents the bending stress that the test piece can withstand when a load is applied, expressed as the load at which the test piece breaks. On the other hand, the "bending degree" in the present invention represents the fragility of the test piece when a certain load is applied to the test piece, expressed as deflection. That is, the "bending" in the present invention is a characteristic value due to displacement, not a characteristic value due to load, and is a characteristic that could not be confirmed by the above-mentioned conventional test method. The present inventors have found that by evaluating the "bending degree" of the present invention, rather than the conventional "bending stress" and "bending modulus", it is possible to evaluate whether a composition is suitable for molding a molded object having fine details that are particularly susceptible to the influence of external forces.
[0063] From the modeling material composition of the present invention, a molded object having such high hardness that it does not sag or deform under its own weight after molding can be obtained. Therefore, the Shore D hardness of the molded object molded from the modeling material composition of the present invention is preferably 65 or more, more preferably 70 or more, even more preferably 72 or more, even more preferably 74 or more, particularly preferably 76 or more, and extremely preferably 78 or more. The Shore D hardness being equal to or greater than the lower limit means that the molded object obtained from the modeling material composition of the present invention has high hardness. The Shore D hardness can be made equal to or greater than the lower limit by, for example, appropriately adjusting the type and / or amount of the polymerizable compound constituting the modeling material composition. The upper limit of the Shore D hardness may usually be 100. The Shore D hardness can be measured according to JIS K7215:1986 "Durometer hardness test method for plastics".
[0064] The method for producing the model material composition of the present invention is not particularly limited. For example, the composition can be produced by uniformly mixing the components constituting the model material composition using a mixer or the like.
[0065] <Inkjet Photopolymerization Composition Set> Although the model material composition of the present invention can model a three-dimensional structure by itself, by using it in combination with a support material for supporting the model material during three-dimensional modeling, it is possible to model a complex shape or a detailed shape with higher accuracy. Therefore, the present invention also covers an inkjet stereolithography composition set comprising the model material composition of the present invention and a support material composition for modeling a support material by inkjet stereolithography.
[0066] (Support material composition) The composition for supporting material is a photocurable composition for supporting material that provides a supporting material by photocuring. After the model material is produced, the supporting material can be removed from the model material by physically peeling it off from the model material or by dissolving the supporting material in an organic solvent or water. The composition for modeling material of the present invention can be used in combination with various compositions conventionally known as a composition for supporting material. However, the composition for supporting material constituting the composition set for stereolithography of the present invention is preferably water-soluble, since the model material is not damaged when the supporting material is removed, the supporting material can be removed cleanly and easily in fine detail, and it is environmentally friendly.
[0067] Such a water-soluble composition for a support material preferably contains a water-soluble monofunctional ethylenically unsaturated monomer, a water-soluble resin, and a photopolymerization initiator. In order to form a support material having both excellent water removability and support power, more specifically, in the above-mentioned composition for a support material, it is preferable that the water-soluble monofunctional ethylenically unsaturated monomer contains a (meth)acrylamide derivative, the above-mentioned water-soluble resin contains at least one selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxytetramethylene group, and the above-mentioned photopolymerization initiator contains an acylphosphine oxide-based photopolymerization initiator.
[0068] Examples of the water-soluble monofunctional ethylenically unsaturated monomer contained in the support material composition include hydroxyl group-containing (meth)acrylates having 5 to 15 carbon atoms [e.g., hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc.], number average molecular weight (M n) 200 to 1,000 hydroxyl group-containing (meth)acrylates [such as polyethylene glycol mono(meth)acrylate, monoalkoxy (carbon number 1 to 4) polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, monoalkoxy (carbon number 1 to 4) polypropylene glycol mono(meth)acrylate, mono(meth)acrylate of PEG-PPG block polymer, etc.], (meth)acrylamide derivatives having 3 to 15 carbon atoms [such as (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-butyl(meth)acrylamide, N,N'-dimethyl(meth)acrylamide, N,N'-diethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-hydroxypropyl(meth)acrylamide, N-hydroxybutyl(meth)acrylamide, etc.], (meth)acryloylmorpholine, etc. These may be used alone or in combination of two or more.
[0069] The content of the water-soluble monofunctional ethylenically unsaturated monomer contained in the support material composition is preferably 19% by mass or more and 80% by mass or less, based on 100% by mass of the total mass of the support material composition. When the content is within the above range, the water removability can be improved without decreasing the support power of the support material.
[0070] The water-soluble resin contained in the composition for support material is for imparting appropriate hydrophilicity to the support material, and by adding it, a support material having both water removability and support power can be obtained. The water-soluble resin preferably contains at least one selected from the group consisting of oxyethylene group, oxypropylene group, and oxytetramethylene group. This is because the water-soluble resin can further improve the water removability without decreasing the support power of the support material. Specific examples of the water-soluble resin include polyoxyalkylene glycols containing at least one selected from the group consisting of oxyethylene group, oxypropylene group, and oxytetramethylene group, such as polyethylene glycol, polypropylene glycol, poly(oxytetramethylene) glycol, polyoxytetramethylene polyoxyethylene glycol, and polyoxytetramethylene polyoxypropylene glycol. The water-soluble resin may be used alone or in combination of two or more.
[0071] The content of the water-soluble resin in the support material composition of the present invention is preferably 15% by mass or more and 75% by mass or less, based on 100% by mass of the total mass of the support material composition. When the content is within the above range, the water removability can be improved without decreasing the support power of the support material.
[0072] The number average molecular weight M of the water-soluble resin n The M of the water-soluble resin is preferably 100 to 5,000. n When the number average molecular weight M of the water-soluble resin is within the above range, the water-soluble resin is compatible with the water-soluble resin before photocuring, but is incompatible with the water-soluble resin after photocuring. As a result, the support material obtained by photocuring the support material composition can have improved self-supporting ability and can have improved solubility in water of the support material. n is preferably 200 to 3,000, more preferably 400 to 2,000.
[0073] As the photopolymerization initiator, the compounds described above may be used as the photopolymerization initiator that may be contained in the modeling material composition. However, from the viewpoint of excellent curability with an LED light source and less coloring of the molded object, it is preferable to include an acylphosphine oxide-based photopolymerization initiator. When the support material composition contains a photopolymerization initiator, the content is preferably 2 to 20 mass%, more preferably 3 to 10 mass%, based on the total mass of the support material composition. When the content of the photopolymerization initiator is equal to or more than the above lower limit, the unreacted polymerization components are sufficiently reduced, and the curability of the support material is easily increased. On the other hand, when the content of the photopolymerization initiator is equal to or less than the above upper limit, it is easy to prevent the unreacted photopolymerization initiator from remaining in the support material.
[0074] The support material composition may contain other additives as necessary, such as a photopolymerization initiator, a water-soluble organic solvent, an antioxidant, a colorant, a pigment dispersant, a storage stabilizer, an ultraviolet absorber, a light stabilizer, a polymerization inhibitor, a chain transfer agent, and a filler.
[0075] From the viewpoint of improving the ejection properties from an inkjet nozzle, the viscosity of the support material composition of the present invention is preferably 3 to 70 mPa s, and more preferably 5 to 60 mPa s at 25° C. The viscosity can be measured using an R100 type viscometer in accordance with JIS Z 8803.
[0076] The method for producing the support material composition of the present invention is not particularly limited, and the composition can be produced, for example, by uniformly mixing the components constituting the support material composition using a mixer or the like.
[0077] <Model and its manufacturing method> The present invention also provides a molded object produced by an inkjet stereolithography method using the model material composition of the present invention or the inkjet stereolithography composition set of the present invention.
[0078] The shaped object of the present invention is produced, for example, by a stereolithography method using the model material composition or the stereolithography composition set of the present invention. In a preferred embodiment of the present invention, the shaped object of the present invention may be produced, for example, by a method including a step of photocuring the model material composition to obtain a model material and a step of photocuring the support material composition to obtain a supporting material, and a step of removing the supporting material from the model material.
[0079] In the above manufacturing method, for example, data on a model material composition that is layered by an inkjet method to form a three-dimensional object, and data on a supporting material composition that supports the three-dimensional object in the process of being produced are prepared based on 3D CAD data of the object to be produced, and slice data is then prepared for discharging each composition using an inkjet 3D printer. After discharging each composition for the model material and the supporting material based on the prepared slice data, a photocuring process is repeated for each layer, thereby producing a modeled object consisting of a cured product of the model material composition (model material) and a cured product of the supporting material composition (supporting material).
[0080] In the above-mentioned manufacturing method, the model material composition is discharged as droplets of 1 pL or more and less than 1 nL, preferably 1 pL or more and 500 pL or less, which makes it possible to obtain a highly precise modeled object with good dimensional accuracy.
[0081] Examples of light for curing the model material composition and the supporting material composition include active energy rays such as far infrared rays, infrared rays, visible light, near ultraviolet rays, ultraviolet rays, electron beams, α rays, γ rays, and X-rays. Among these, near ultraviolet rays or ultraviolet rays are preferred from the viewpoint of ease and efficiency of the curing operation.
[0082] Examples of light sources include conventionally known high-pressure mercury lamps, metal halide lamps, UV-LEDs, etc. Among these, LEDs are preferred from the viewpoints of downsizing the equipment and low power consumption. The amount of light irradiated at one time is 200 to 500 mJ / cm from the viewpoints of hardness and dimensional accuracy of the molded object. 2When using a UV-LED as the light source, it is preferable to use one with a central wavelength of 385 to 415 nm, since the light can easily reach deep layers and improve the hardness and dimensional accuracy of the molded object.
[0083] From the viewpoint of modeling accuracy, it is preferable that the thickness of each layer constituting the three-dimensional object is thin, but from the viewpoint of the balance with modeling speed, the thickness is preferably 5 to 30 μm.
[0084] The obtained shaped object may be a combination of a model material and a supporting material. In this case, the supporting material is removed from the shaped object to obtain a shaped object that is a model material. The supporting material is preferably removed, for example, by immersing the obtained shaped object in a removal solvent that dissolves the supporting material to dissolve and remove the supporting material, or by immersing the supporting material in the removal solvent to soften it and then removing it from the surface of the model material with a brush or the like. The removal solvent for the supporting material may be water or a water-soluble solvent, such as a glycol-based solvent or an alcohol-based solvent. These may be used alone or in combination.
[0085] A molded object can be obtained by the above steps. A molded object produced using the model material composition of the present invention or the stereolithography composition set of the present invention has the properties of being resistant to bending while maintaining high hardness. EXAMPLES
[0086] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.
[0087] (Preparation of Model Material Composition) Details of the components constituting the model material compositions used in the examples and comparative examples are shown in Table 1.
[0088] [Table 1]
[0089] (Preparation of Model Material Composition) According to the compositions shown in Tables 2 and 3, the components constituting each model material composition were mixed uniformly using a mixing and stirring device. After stirring, the mixture was suction filtered using a glass filter (manufactured by Kiriyama Seisakusho) to prepare the model material compositions of the examples and comparative examples.
[0090] [Table 2]
[0091] [Table 3]
[0092] (viscosity) The viscosity of the model material compositions of the examples and comparative examples was measured using a TV-22 viscometer (manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and a cone rotation speed of 20 rpm.
[0093] (Glass transition temperature of model material composition) The glass transition temperature (Tg) of the model material compositions of the examples and comparative examples was measured using a TG-DTA2000S ThermoPlus Evo II and a DSC8230 (manufactured by Rigaku Corporation). The measurement was performed at a temperature rise rate of 10°C / min and a measurement temperature range of -60°C to 200°C.
[0094] (bending degree) 1. Preparation of test specimens for evaluation Silicone rubber sheet (thickness 2 mm, Togawa Rubber Co., Ltd. food industry rubber sheet (K-125 <50> ) was cut into a rectangle of 60 mm x 30 mm, and then a rectangle of 40 mm x 5 mm was cut out from the center of the rectangle to create a rectangular frame. Next, the rectangular frame was pressed and attached onto a PET film (Lumirror S-10#25, thickness 23 μm) manufactured by Toray Industries, Inc., to create a mold. 0.5 g of the model material composition of the Examples and Comparative Examples was poured into the mold frame, and the composition was exposed to ultraviolet light irradiation equipment (LED lamp, 385 nm, irradiation amount: 4000 mJ / cm2). 2The cured product was removed from the silicone rubber sheet (rectangular frame) to prepare evaluation test pieces for the examples and comparative examples.
[0095] 2.Flexibility test A Nabeya vise was used with the jaws spaced 30 mm apart, and the test specimen prepared by the above procedure was placed on it so that the center of the jaws and the center of the test specimen were aligned. A 1 mm thick stainless steel piece was used to press the center of the test specimen vertically downward with a load of 5 kg, and the amount of displacement just before the test specimen was broken was measured. The upper surface of the test specimen was used as the reference, and the distance to the bottom end of the stainless steel piece was used as the amount of displacement. As the amount of displacement of the stainless steel piece increases, the horizontal width of the test specimen placed in the vise becomes smaller, so when the amount of displacement exceeded 10 mm, the interval between the jaws of the vise was changed to 20 mm, and when the amount of displacement exceeded 15 mm, the interval between the jaws of the vise was changed to 10 mm, and the center of the test specimen was similarly pressed down vertically with the stainless steel piece. The test was carried out under conditions of 25°C and 50% RT.
[0096] (Shore D hardness) The Shore D hardness of the cured product of the model material composition of the Examples and Comparative Examples was measured by pouring 3.9 g of the model material composition of the Examples and Comparative Examples into a 25 mm × 25 mm × 5 mm mold made of a silicone rubber sheet (thickness 5 mm), and subjecting the mold to an ultraviolet irradiation device (LED lamp, 385 nm, irradiation light amount: 4000 mJ / cm 2 The cured product was used as a measurement sample and measured in accordance with JIS K7215:1986 "Durometer hardness testing method for plastics".
[0097] (Bending stress) The bending stress of the cured products of the model material compositions of the Examples and Comparative Examples was measured in accordance with "9.1 Bending stress" of JIS K7171:2016 "Plastics - Determination of bending properties".
[0098] (Flexural modulus) The flexural modulus of the cured product of the model material composition in the examples and comparative examples was measured in accordance with "9.3 Flexural modulus" of JIS K7171:2016 "Plastics - Determination of flexural properties".
[0099] The results are shown in Tables 4 and 5. In the tables, "-" indicates that the measurement was not performed. [Table 4]
[0100] [Table 5]
[0101] As can be seen from the results of Tables 4 and 5, the objects molded from the modeling material compositions of the Examples were strong in bending despite their high hardness. On the other hand, the objects molded from the modeling material compositions of the Comparative Examples were insufficient in at least one of the degree of bending and hardness. In addition, the evaluation results of Comparative Example 3 and the Examples show that even if the bending stress and bending modulus are large, the objects do not necessarily have excellent bending properties.
Claims
1. A composition for modeling a model material by inkjet stereolithography, comprising: 60% by mass or less of a monofunctional ethylenically unsaturated monomer (A) having a homopolymer glass transition temperature of 50° C. or higher; 10% by mass or more and 50% by mass or less of a bifunctional ethylenically unsaturated monomer (B) having a homopolymer glass transition temperature of 50° C. or more; 5% by mass or more and 20% by mass or less of a polyfunctional thiol monomer (C); A photopolymerization initiator (D) is contained, The content of trifunctional or higher ethylenically unsaturated monomers is less than 10% by mass based on the total mass of the composition. A model material composition, wherein a molded object made from the composition has a glass transition temperature of 60°C or higher.
2. The composition of claim 1 , wherein the content of the oligomer is 20% by weight or less based on the total weight of the composition.
3. The composition of claim 2 , wherein the oligomer is at least one selected from the group consisting of a urethane (meth)acrylate oligomer, an epoxy (meth)acrylate oligomer, and a polyester (meth)acrylate oligomer.
4. The composition of claim 1 , wherein the multifunctional thiol monomer (C) comprises a trifunctional or tetrafunctional thiol monomer.
5. The composition of claim 4, wherein the trifunctional thiol monomer comprises 1,3,5-tris(2-(3-sulfanylbutanoyloxy)ethyl)-1,3,5-triazinane-2,4,6-trione or trimethylolpropane tris(3-mercaptopropionate).
6. The composition of claim 4, wherein the tetrafunctional thiol monomer comprises pentaerythritol tetrakis(3-mercaptobutyrate) or pentaerythritol tetrakis(3-mercaptopropionate).
7. The composition according to claim 1 , wherein the content of the photopolymerization initiator (D) is 0.1% by mass or more and 15% by mass or less based on the total mass of the composition.
8. 2. The composition according to claim 1, wherein the bending degree calculated as the deflection when the center of a 40 mm x 5 mm x 2 mm test piece is pressed with a load of 5 kg at 25°C and 50% RT is 12 mm or more.
9. The composition of claim 1 , wherein a shaped object formed from the composition has a Shore D hardness of 65 or greater.
10. The composition of claim 1 , wherein said component (A) comprises isobornyl acrylate.
11. The composition of claim 1 , wherein component (A) comprises acryloyl morpholine.
12. The composition of claim 1 , wherein the light source used in the inkjet stereolithography is an LED.
13. A shaped object formed from the composition of claim 1.
14. 13. An inkjet stereolithography composition set, comprising the composition according to claim 1 and a support material composition for forming a support material by inkjet stereolithography.
Citation Information
Patent Citations
Photocurable composition
JP2007530724A
